Secular and Christian leadership in Corinth : a socio-historical and exegetical study of 1 Corinthians 1-6 - Clarke, Andrew D. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1993)
This volume traces the influences of first century Corinthian secular leadership on local church leadership as reflected in 1 Corinthians 1-6. It then shows how Paul modifies the Corinthian understanding of church leadership. By comparing secular leadership in first century Corinthian society with leadership in the Corinthian church, it has been argued that one of Paul's major concerns with the church in Corinth is the extent to which significant members in the church were employing secular categories and perceptions of leadership in the Christian community. This volume has adopted the method of assessing the New Testament evidence in the light of its social and historical background. Both literary and non-literary sources, rather than modern sociological models, were employed in making the comparison.